Evaluation of the published kinase inhibitor set to identify multiple inhibitors of bacterial ATP-dependent mur ligases. (1st January 2019) - Hrast, Martina; Rožman, Kaja; Ogris, Iza; Škedelj, Veronika; Patin, Delphine; Sova, Matej; Barreteau, Hélène; Gobec, Stanislav; Grdadolnik, Simona Golič; Zega, Anamarija
Abstract: The Mur ligases form a series of consecutive enzymes that participate in the intracellular steps of bacterial peptidoglycan biosynthesis. They therefore represent interesting targets for antibacterial drug discovery. MurC, D, E and F are all ATP-dependent ligases. Accordingly, with the aim being to find multiple inhibitors of these enzymes, we screened a collection of ATP-competitive kinase inhibitors, on Escherichia coli MurC, D and F, and identified five promising scaffolds that inhibited at least two of these ligases. Compounds 1, 2, 4 and 5 are multiple inhibitors of the whole MurC to MurF cascade that act in the micromolar range (IC50, 32–368 µM). NMR-assisted binding studies and steady-state kinetics studies performed on aza-stilbene derivative 1 showed, surprisingly, that it acts as a competitive inhibitor of MurD activity towards D-glutamic acid, and additionally, that its binding to the D-glutamic acid binding site is independent of the enzyme closure promoted by ATP.